A new approach of using Lorentz force to study single-asperity friction inside TEM. (10th September 2021) - Lu, Huanhuan; Wang, Zhangjie; Yun, Di; Li, Ju; Shan, Zhiwei
Graphical abstract: Highlights: The Lorentz-force-actuated approach was developed for friction tests inside TEM. The relative motion commenced with the plastic deformation near the interface. The maximum friction force arrived, exactly followed by the interfacial sliding. The relative motion took place before the arrival of maximum friction force. Abstract: Taking advantage of the magnetic field inside transmission electron microscope (TEM), a unique Lorentz-force-actuated method for quantitative friction tests was developed via a commercial electromechanical holder. With this approach, a submicron-sized silver asperity sliding on a tungsten flat punch was actuated by Lorentz force due to electrical current through the punch, with the normal force imposed by the built-in transducer of the holder. The friction force was determined by tracking the elastic deflection of the fabricated cantilever from in situ video. Through correlating the friction behavior with the microstructural evolution near the silver-tungsten interface, we revealed that even when the relative motion commenced with the plastic deformation of the silver asperity, the interface can still sustain the further increasing static friction force. Exactly following the arrival of the maximum static friction force, the sliding occurred at the interface, indicating the transition from static to dynamic friction. This work enriches our understanding of the underlying physics of the dynamic friction process for metallic friction behavior.